2022
DOI: 10.1155/2022/7187356
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Xylobezoar Treated with Continuous Enteral Coca-Cola® Infusion

Abstract: Xylobezoar is a rare clinical condition in which undigested paper becomes trapped in the gastrointestinal tract causing varying degrees of gastrointestinal obstruction. This condition can be suspected in children with a history of gastric surgeries, decreased gastrointestinal motility, or pica. Xylobezoar presents with symptoms ranging from chronic abdominal pain to gastrointestinal perforation. Surgical intervention is often required as endoscopic removal is challenging and not always successful. Chemical dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…One study has reported successful treatment of xylobezoar with nasogastric infusion of Coca-Cola. 10 In conclusion, our case report highlights the challenges and complexities involved in managing a rare case of xylobezoarinduced pancolonic obstruction in a patient with pica secondary to severe iron deficiency anemia, ultimately resulting in a fatal outcome. It underscores the importance of increased awareness, early intervention, and interdisciplinary management in such cases.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…One study has reported successful treatment of xylobezoar with nasogastric infusion of Coca-Cola. 10 In conclusion, our case report highlights the challenges and complexities involved in managing a rare case of xylobezoarinduced pancolonic obstruction in a patient with pica secondary to severe iron deficiency anemia, ultimately resulting in a fatal outcome. It underscores the importance of increased awareness, early intervention, and interdisciplinary management in such cases.…”
Section: Discussionmentioning
confidence: 81%
“…One study has reported successful treatment of xylobezoar with nasogastric infusion of Coca-Cola. 10 …”
Section: Discussionmentioning
confidence: 99%
“…This is particularly relevant in specialized healthcare facilities with prompt access to gastroenterology and surgical support. Physicians should be cautious of the potential risk of partially dissolved bezoars causing small intestinal obstructions during the treatment process [ 4 ]. Efficacy was noted in 54.8% (n = 17) of our study cases.…”
Section: Discussionmentioning
confidence: 99%
“…Managing phytobezoars typically involves conservative approaches such as administering proteolytic enzymes, cellulase, and carbonated beverages orally or through gastric lavage, sodium bicarbonate (NaHCO 3 ) powder, aspiration, endoscopic fragmentation, and, in refractory cases, surgery [ 4 , 5 ]. The efficacy of these treatments varies significantly, especially in diospyrobezoars, which are implicated in some countries as a major etiological agent for phytobezoar development.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,8,9 Trichobezoar is rare condition seen almost exclusively in young women with certain psychiatric disorders. 4,5 This type of bezoar is resistant to enzymatic degradation and endoscopic fragmentation, so surgery is treatment of choice. Psychiatric treatment is also necessary to prevent recurrences.…”
mentioning
confidence: 99%